Ethnomedical Knowledge of Plants Used in Traditional Medicine in Mampa Village, Haut-Katanga Province, Democratic Republic of the Congo - Bashige Chiribagula Valentin; Biayi Benaja Martin; Bakari Amuri Salvius; Lumbu Simbi Jean Baptiste (The Scientific World Journal, 2025)
The inhabitants of the village of Mampa have developed a rich corpus of knowledge and practices for treating pathologies using plants that are worthy of preservation, perpetuation, and promotion. They draw on the region’s rich biodiversity, particularly in the Miombo clear forest. However, to date, no documentation of their ethnomedicinal knowledge exists. This descriptive cross-sectional study was conducted between November 2022 and October 2023. It employed a direct, face-to-face interview with the Mampa village population and a guide questionnaire. A total of 400 respondents were included in the study (sex ratio M/F=0.9; mean age: 48.0±4.0 years; experience: 14.5±2.0 years), and the majority (93.8%) reported that they learned about plants from their families. These individuals mainly use plants as a first-line treatment (100%) and provided information on 38 plants. The most commonly cited species were Anisophyllea pomifera and Brachystegia boehmii with 46 citations, while the most commonly used plant was Landolphia kirkii with six recorded uses. This is the first report of Entandrophragma delevoyi and Pterocarpus brenanii as medicinal plants. Most of these plants are trees, comprising 29 from 23 genera belonging to 24 families, with a notable prevalence of Fabaceae (10 plants). Thirty-two diseases are indicated for treatment, with a predominance of gastrointestinal disorders (8 recipes, 7 plants, 152 citations). The root is the most used organ, with 21 recipes and 14 plants, while decoction is the most common preparation method, with 41 recipes and 19 plants. This study’s findings indicate that a significant number of medicinal plants are used in traditional Mampa medicine to treat various diseases. Some of these species are endemic to the Miombo biodiversity, while others are shared with other cultures and regions. A series of pharmacological studies are currently underway to validate some of the reported plant indications.